Pharmacokinetics, Safety and Efficacy of Maraviroc in Treatment-experienced Pediatric Patients Infected With CCR5-Tropic HIV-1. Issue 5 (May 2018) - Giaquinto, Carlo; Mawela, Muthuhadini Patience; Chokephaibulkit, Kulkanya; Negra, Marinella Della; Mitha, Ismail Haroon; Fourie, Jan; Fang, Annie; van der Ryst, Elna; Valluri, Srinivas Rao; Vourvahis, Manoli; Zhang-Roper, Rebecca Yanhui; Craig, Charles; et al.
Abstract : Background: Maraviroc is a CC-chemokine receptor 5 antagonist approved to treat adults infected with CC-chemokine receptor 5–tropic (R5) HIV-1. Study A4001031 was conducted to evaluate the pharmacokinetics, safety and efficacy of maraviroc in combination with optimized background therapy in treatment-experienced pediatric patients infected with R5 HIV-1 and support registration of maraviroc for pediatric use. Methods: This is an open-label, 2-stage, age-stratified, noncomparative multicenter study. One-hundred and three participants were enrolled into 4 age/formulation cohorts and dosed twice daily. Initial doses were determined by body surface area and optimized background therapy, based on drug interactions with maraviroc in adults. Dose adjustment and pharmacokinetic reevaluation occurred if the average concentrations ( C avg ) at Week 2 were <100 ng/mL (Stage 1—dose finding). Results: Data from the Week 48 analysis demonstrated that 49/50 Stage 1 participants rolling over into Stage 2 (safety and efficacy) achieved C avg ≥100 ng/mL. Doses were identified that achieved similar concentration ranges to those seen in adults. The majority (90/103) received optimized background therapy containing potent cytochrome P450 3A inhibitors. Maraviroc was well tolerated and the safety and efficacy were comparable to those of adults. All cohorts had a mean decrease from baseline in HIV-1 RNA of >1 log10 . Increases from baseline in the median CD4+ cell count and percentage were seen for all age groups. Conclusions: The maraviroc dosing strategy resulted in participants achieving the target C avg, with exposure ranges similar to those observed in adults on approved doses. The safety and efficacy of maraviroc in this pediatric population were comparable to those seen in adults. Abstract : Supplemental Digital Content is available in the text.